Spectacular bodies : gender, genre, and the action cinema - Tasker, Yvonne, 1964- (Comedia., 1993)
While films such as Rambo, Thelma and Louise and Basic Instinct have operated as major points of cultural reference in recent years, popular action cinema remains neglected within contemporary film criticism. Spectacular Bodies unravels the complexities and pleasures of a genre often dismissed as `obvious' in both its pleasure and its politics, arguing that these controversial films should be analysed and understood within a cinematic as well as a political context. Yvonne Tasker argues that today's action cinema not only responds to the shifts in gendered, sex.